2016
DOI: 10.1089/mab.2015.0056
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab-Resistant Luminal B Breast Cancer Cells Show Basal-Like Cell Growth Features Through NF-κB-Activation

Abstract: A major clinical problem in the treatment of breast cancer is mortality due to metastasis. Understanding the molecular mechanisms associated with metastasis should aid in designing new therapeutic approaches for breast cancer. Trastuzumab is the main therapeutic option for HER2+ breast cancer patients; however, the molecular basis for trastuzumab resistance (TZR) and subsequent metastasis is not known. Earlier, we found expression of basal-like molecular markers in TZR tissues from patients with invasive breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Even in the case that the same cell line, BT-474, is used, different mechanisms have been reported. For example, we had found that nuclear factor-kappa B (NF-kappaB) was constitutively activated in the BT-474-R cells [ 23 ]. In the process of acquiring the resistance, several different molecular alterations may emerge depending on the culture condition in vitro and microenviromental conditions in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in the case that the same cell line, BT-474, is used, different mechanisms have been reported. For example, we had found that nuclear factor-kappa B (NF-kappaB) was constitutively activated in the BT-474-R cells [ 23 ]. In the process of acquiring the resistance, several different molecular alterations may emerge depending on the culture condition in vitro and microenviromental conditions in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…HER2-positive human breast cancer cell line BT-474 (catalog number: HTB-20) was purchased from American Type Culture Collection (Manassas, VA, USA). BT-474-R was previously established by treating BT-474 with increasing doses of trastuzumab (from 0.1 μg/mL to 40 μg/mL) for 10 months [ 23 ]. To obtain trastuzumab/lapatinib-dual resistant BT-474 (named as BT-474-RL2), BT-474-R was additionally treated with increasing doses of lapatinib (from 0.1 μM to 5 μM) for 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bortezomib treatment demonstrated to induce apoptosis and to act synergistically with trastuzumab in this breast cancer subtype (258,259). In the case of HER2-positive ER-positive breast cancer cell lines resistant to trastuzumab, the NF-κB pathway showed to be constitutively activated and its blockade improved the tumor response to trastuzumab (260).…”
Section: Trastuzumabmentioning
confidence: 99%
“…In recent years, other potential mechanisms of acquired resistance to TRA in Her2-like BC have been discovered and studied, such as the increased phosphorylation of the nuclear factor kappa B (NF-kB) p65 subunit (20, 21). Understanding the molecular mechanisms that contribute to the acquired resistance will ultimately allow for the identification of biomarkers that can be used to predict response to TRA therapy, as well as the identification of molecular targets for new therapeutics development.…”
Section: Introductionmentioning
confidence: 99%